Finance-Growth Linkage and Risk Diversification. Evidence from OECD Countries - Franz R. Hahn (Austrian Institute of Economic Research (WIFO), 2006)
Empirical evidence is increasingly emphasising the positive influence of financial markets on the level and the rate of growth of a country's per-capita income. Theoretically, the rationale for the finance-growth nexus appears to be straightforward: in imperfect economies, financial markets provide valuable services such as mobilising savings, diversifying risks, allocating savings to investments, and monitoring the allocation of managers. By performing these services financial markets work as a very important catalyst of economic growth. However, little insight has so far been provided by empirical research as to which of these financial services is most critical for economic growth. Using a panel data set covering 20 OECD countries over the period 1970 through 2000 we present empirical evidence which suggests that the finance-growth nexus in industrialised countries be significantly strengthened by the improvement of risk management and risk diversification made possible by financial innovation and advancement.
Keywords: 330; economic growth; risk management; risk diversification; financial innovation; panel analysis; Finanzsektor; Wirtschaftswachstum; Schätzung; OECD-Staaten